(2+1) Resonance-enhanced multiphoton ionization (REMPI) and (2+1 ') mass-analyzed threshold ionization (MATI) spectroscopy of H2O - Dickinson, H; Mackenzie, S; Softley, T (2000)
Rotationally resolved MATI spectra of H2O, recorded using two-colour (2 + 1') multiphoton excitation via the C state, are reported. The spectroscopy provides a possible route to clean state-selection of rovibronic levels of the H2O+ ion. The rotational line intensities observed in the spectra are discussed in relation to previous photoelectron spectra and theoretical calculations. The observation of intense ΔK(a) = even transitions is attributed to a large contribution to the transition moment from an nf ← nd component. Room temperature and jet-cooled (2 + 1) REMPI spectra of H2O are also reported for the region 80000-92000 cm-1. These involve two-photon transitions from the ground X 1A1 state to various vibrational levels of the C 1B1, D' 1B1 and D'' 1A2 states as well as the first linear 1B2 state.